A Functional Vegetable Option: An Exploratory Study Testing Kimchi Variation for Acceptance among Consumers. Issue 6 (2nd November 2021) - Bai, Yeon; Feldman, Charles; Li, Yanyan; Keys, Ki; Overgaard, Kaitlin
ABSTRACT: This pilot study aimed to potentially increase the consumption of cancer-preventative sulforaphane, available in broccoli, by introducing this vegetable in novel kimchi products. A panel of mostly Korean-borne or descendant kimchi consumers assessed four kimchi variations for texture, flavor, and overall acceptance. A mixed-method approach utilized hedonic scoring, FaceReader ® software, and interviews. Large-cut broccoli kimchi scored highest (7.74/10) for crispness (95% CI [−2.79, −0.27]) as well as saltiness, bitterness, pungency, and intention to try. Three-global themes emerged from interviews: sensory uniqueness (29%); delicious/good (36%); and interest/novelty (36%). Participants' favorable acceptance gives impetus for innovative strategies combining functional vegetables with traditional ingredients.